ANALISIS DAN PENINGKATAN KUALITAS LAYANAN PADA JARINGAN KOMPUTER NIRKABEL BADAN PENGHUBUNG LAMPUNG DALAM MENDUKUNG TUGAS PEMERINTAHAN: Bahasa Indonesia - Desi Ramayanti; Syarifudin (JSAI (Journal Scientific and Applied Informatics), 2024)
This study aims to evaluate the quality of internet network in Badan Penghubung Lampung using the TIPHON standard. The assessment is conducted by measuring several network performance parameters, including bandwidth, throughput, delay, and packet loss. The measurements are carried out for four days during office hours using the Axence Nettools 5 and speedtest.net applications. The collected data is then analyzed to obtain the average values for each parameter. The measurement results indicate that the overall quality of the internet network in Badan Penghubung Lampung is classified as very good. The average throughput value is 1,636 Kbps, which exceeds the TIPHON standard. The delay parameter has an average of 40.17 ms, which also meets the TIPHON standard. Meanwhile, the packet loss has an average of 2.75%, which is well below the maximum limit set by the TIPHON standard. However, this study also shows that the throughput value can be influenced by varying weather conditions, with the lowest data transfer speed occurring on the last day of the study. Therefore, for a more comprehensive evaluation of network quality, it is recommended to consider other parameters such as jitter, reliability, and availability.